Experimental and numerical fatigue assessment of duplex welded transversal stiffeners - Karabulut, B; Lombaert, G; Debruyne, D; Rossi, B (Elsevier, 2020)
Fatigue is mostly the governing design criterion in girder steel bridges due to the presence of critical welded details. In this research, the hot spot stresses in welded cruciform duplex stainless steel joints are measured experimentally using digital image correlation as well as traditional strain gauges. They are also computed via FEM. The deduced fatigue lives are then compared to each other as well as to small-scale cyclic test results and to a series of literature data on similar welded details. The comparison highlights very consistent results and demonstrates applicability of the hot spot stress method to welded duplex details.